(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
The banking sector is one of the key economic sectors of the economies of the countries and represent the cornerstone of the pillars of economic development in modern societies, and in the light of this, the research analyzed the financial situation of the International Kurdistan Bank for investment and development . As a result, the research targeted to analyze the financial realities of the International Kurdistan Bank for investment and development for the period (2005-2014), and through the research results, it has proved that the total revenue in the constant increase during the study of the bank , with an average overall growth rate (229.707%), and for the revenues from financing and investments, they are volatile, but it is noted that the average overall growth rate was positive and amounted to (4965.745%), and with respect to a net profit after tax, the bank made a profit in each year of the study period (with the exception of 2005), this has reached the average overall growth rate (68.072%) and finally the research recommended a series of important recommendations, including a review of the deposit investment ratio to achieve the objectives of the bank and in the forefront of them the economic profit, as well as encouraging community members to deposit their savings, and requires the bank to diversify revenue.